Health Conditions of Elderly (Secondary Data Analysis of 2021 Social-Economic Survey Data) - Anindya Puspita Maheswari; Rifqatussa'adah Rifqatussa'adah; Fathul Jannah (Junior Medical Journal, 2023)
In Indonesia during 2019, the elder population reached 13,4% and is predicted to increase gradually from year to year. In general, the elderly age group is a phase in which most individuals have already got a decrement in health condition, both physically and psychologically. The purpose of this study is to give an overview about the health condition of the elderly. This research method is quantitative using descriptive research type. The research design used in this study is a cross-sectional research design. The sampling method for this study is purposive sampling. The population under this study are SUSENAS 2021 Indonesia with a sample of 18.352 resident within the category of elder age group in Indonesia. The research instrument for this paper is the questionnaire result from SUSENAS 2021. The instrument in this study was the results of the 2021 SUSENAS questionnaire. The result of this study shows that 67,4% of elder age group citizens in Indonesia are within the scope of healthy condition. The result of this research test shows that the health condition of the elder age group is affected by age (p=0,000), education (p=0,000), employment (p=0,000), marital status (p=0,000), social activity (p=0,000), health facility services (p=0,000),community activities (p=0,000), and the environmental factor (p=0,000). Meanwhile, gender did not find a related signicant. The conclusion of this study is that in Islam, the elderly have a high position in society, in particular, from the point of view that they are a source of knowledge and experience, as well as information and thoughts. therefore, they must be respected, loved, cared for and given priority to their health, it is essential that they be harmed, neglected, aware of their health, and given proper attention.